Relationship between antioxidant capacity, chlorogenic acids and elemental composition of green coffee. (November 2016) - Jeszka-Skowron, Magdalena; Stanisz, Ewa; De Peña, Maria Paz
Abstract: Antioxidant capacity of green coffee infusions (Arabica and Robusta of different geographical origin) has been studied e.g. with the use of Folin-Ciocalteu assay (the average: 1043 ± 577 mg GAE/L). The highest antioxidant capacity as well as concentration of three main 5-, 4- and 3- caffeoylquinic acids were determined for Robusta coffee brews. According to assay used, steaming and decaffeination of Vietnam coffee beans altered the antioxidant capacity as well as the concentration of chlorogenic acids in the infusions. Additionally, the method of Cd, Cu, Mn, Pb and Se determination in green coffee beans and their infusions was optimized with the use of graphite furnace atomic absorption spectrometry. The average concentration of metals in green coffee beans was (mg/kg): Cd (0.013 ± 0.008), Cu (13.3 ± 2.8), Mn (24.1 ± 8.7), Pb (0.023 ± 0.005), Se (0.028 ± 0.010), respectively. The average leachabilities of Mn and Cu were established as 31.5% and 62.3%, respectively. The Cd, Pb and Se concentrations in the infusions were below the limits of detections. Highlights: Green Robusta coffees possessed higher antioxidant capacity than Arabica. Green Robusta brews contained more 4- & 3-caffeoylquinic acids than Arabica. Cu, and Mn were detected in green coffee beans and brews. No Cd, Pb, and Se could be detected in green coffee brews.